The Role of Bugis Cultural Values in Realizing Religious Moderation - Ahmad Ridha (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2023)
The development of religious moderation is an urgent consensus, both conceptually and practically, to give birth to a society living side by side in harmony and tolerance towards fellow human beings. The concept of moderation in achieving a tolerant position in the cultural values of ethnic groups is an important indicator to complement and expand the study of moderation in religion and social affairs. The purpose of this research is to reveal the local cultural values of the Bugis community in building the concept of moderation in religion. The method in this study is to use ethnographic studies, an infiltration approach between Islamic teachings and the local culture of the community, and data collection techniques using in-depth interview techniques with Muslim and non-Muslim communities. The results of the study show (1) internalization of an attitude or society that puts human values between fellow believers and different ethnic groups around it; (2) internalization of sipakalebbi, community respect for fellow believers of different beliefs, and living in harmony and side by side. (3) internalization sikaunge that Bugis culture reminds each other of as a basis for anticipating repressive actions and intolerant attitudes. This article has implications for the conceptual development of religious and social moderation by prioritizing the approach of socio-cultural values in society without reducing religious values themselves. In addition, the implications of this research can also provide an alternative to the process of fostering religious and social moderation to create a tolerant atmosphere based on regional geography, culture, and other habits